2006
DOI: 10.1111/j.1365-2265.2006.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parasellar extension of macroprolactinomas defined by magnetic resonance imaging on their responsiveness to dopamine agonist therapy

Abstract: Parasellar extension of macroprolactinomas, assessed on the basis of strict MRI criteria, may predict a negative response to DA. The responsiveness of noninvasive macroprolactinomas (over 90%) is similar to that reported in microprolactinomas, whereas invasive tumours are resistant to treatment in more than 50% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 29 publications
(43 reference statements)
1
17
0
5
Order By: Relevance
“…It has been demonstrated that DA-resistant patients tend to be younger males with larger or more invasive adenomas [3133]. A recent study on macroprolactinomas in children and adolescents indicated that DA resistance is associated with higher PRL levels and larger tumor sizes, which are closely linked together [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that DA-resistant patients tend to be younger males with larger or more invasive adenomas [3133]. A recent study on macroprolactinomas in children and adolescents indicated that DA resistance is associated with higher PRL levels and larger tumor sizes, which are closely linked together [34].…”
Section: Discussionmentioning
confidence: 99%
“…Considering these findings, the prolactin normalization remains an important and easily assessable end-point. Up to now, dose adjustments or medication changes have been mainly guided by attempts to obtain normalization of the hormonal levels [2,14,15]. Radiotherapy may be performed for radiologic or biochemical resistance cases.…”
Section: Discussionmentioning
confidence: 99%
“…³ ñï³âàâò. ïîêàçàëè, ùî ïàðàñåëÿðíå ðîç-ïîâñþäaeåííÿ ìàêðîïðîëàêòèíîì çà äàíèìè ÌÐÒ ãîëîâíîãî ìîçêó ìîaeå áóòè ïðåäèêòîðîì íåãà-òèâíî¿ â³äïîâ³ä³ íà òåðàï³þ ÀÄ [59]. Ïîçèòèâíó â³äïîâ³äü íà òåðàï³þ ÀÄ áóëî â³äçíà÷åíî ó 90% âèïàäê³â äëÿ õâîðèõ ³ç íå³íâàç³éíèìè ìàêðî-ïðîëàêòèíîìàìè ³ ó 50% -ç ³íâàç³éíèìè àäåíî-ìàìè.…”
Section: сучасні погляди на діагностику та лікування пролактиномunclassified
“…³äïîâ³äíî ï³ä ö³ëêîâèòîþ ðåçèñòåíòí³ñòþ ðî-çóì³þòü â³äñóòí³ñòü áóäü-ÿêîãî åôåêòó â³ä ÀÄ, ï³ä ÷àñòêîâîþ -íåìîaeëèâ³ñòü äîñÿãíåííÿ íîð-ìîïðîëàêòèíå쳿 àáî çìåíøåííÿ îá'ºìó ã³ïîô³-çà ìåíøå, í³ae íà 50%. Ðåçóëüòàòè êë³í³÷íèõ äîñë³äaeåíü ïîêàçàëè, ùî ðåçèñòåíòí³ñòü äî áðî-ìîêðèïòèíó òà êàáåðãîë³íó òðàïëÿºòüñÿ ïðèáëèç-íî ó 30% ³ 10-15% âèïàäê³â â³äïîâ³äíî [67].…”
Section: сучасні погляди на діагностику та лікування пролактиномunclassified
See 1 more Smart Citation